Development of an Extension ‘Primer’ on Tree Registration Policy in Leyte: An Example of a Collaborative Material Design - Gordon, Melissa; Gravoso, Rotacio; Mangaoang, Eduardo; Balbarino, Edwin (Annals of Tropical Research, 2007)
Tree registration in the Philippines helps meet the legal requirements for harvesting and transport of timber, and is encouraged by the Philippine Government. To help improve information flow an extension primer was developed. The primer contains basic information on tree registration, harvesting, log transport and marketing. The development process involved input from staff of the Philippine Department of Environment and Natural Resources, tree farmers, furniture dealers, the Philippine National Police, the World Agroforestry Centre, Visayas State University and the University of Queensland. Key stakeholders were brought together at three workshops to review policy information and explore the interactions between, and differing opinions of, the various stakeholders. The primer has been distributed widely. Positive feedback has been obtained, although testing has shown that further improvements are possible. A revised version of the primer is to be produced.